Analisis Tingkat Literasi Keuangan Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Negeri Padang - Rasyid, Rosyeni (Jurnal Kajian Manajemen Bisnis, 2012)
The aimed of research to know how students’ financial literacy level and money management ability of Management Study Program of Faculty of Economics, State University of Padang. It’s used descriptive and asosiatif research. Data primary is used to this research with 100 sample. Hypotesis test use multiples linear regression analysis. The results of research found the student’s level is moderate in financial literacy with  score 3.43 (69%); spending literation with score 3.46 (69%); credit literation with score 3.1 (62%); saving literation with score 3.39 (67%), and  investment literation with score 3.79 (76%). The results also showed that money management ability is moderate level. Result of research show that financial literacy influential significant positively to  money management ability student.